2015
DOI: 10.1080/00221325.2015.1024198
|View full text |Cite
|
Sign up to set email alerts
|

Abstracting Sequences: Reasoning That Is a Key to Academic Achievement

Abstract: The ability to understand sequences of items may be an important cognitive ability. To test this proposition, 8 first-grade children from each of 36 classes were randomly assigned to four conditions. Some were taught sequences that represented increasing or decreasing values, or were symmetrical, or were rotations of an object through 6 or 8 positions. Control children received equal numbers of sessions on mathematics, reading, or social studies. Instruction was conducted three times weekly in 15-min sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 16 publications
7
57
0
2
Order By: Relevance
“…Finally Pasnak et al (2015) replicated the study of Kidd et al (2014) and partially replicated the results. The children taught either complex patterns or reading outscored the other control children on the TERA and TOWRE reading tests, but not on the GORT.…”
Section: Instruction On Complex Patternssupporting
confidence: 81%
See 1 more Smart Citation
“…Finally Pasnak et al (2015) replicated the study of Kidd et al (2014) and partially replicated the results. The children taught either complex patterns or reading outscored the other control children on the TERA and TOWRE reading tests, but not on the GORT.…”
Section: Instruction On Complex Patternssupporting
confidence: 81%
“…Identifying a pattern rule via induction and applying it via deduction to a new pattern which could be solved by the same rule could be the central mechanisms involved in patterning. Pasnak et al (2015) suggested that in addition to Gf, two other CHC components, Gq (quantitative reasoning) and Grw (a component of reading ability) are likely to be involved in understanding complex patterns, given the impact of instruction on such patterns on early mathematics and reading. If this suggestion is correct, the mechanisms involved would be three components of the CHC, currently the most widely accepted theory of intelligence.…”
Section: Components Of Intelligencementioning
confidence: 99%
“…The patterning instruction was modeled after the interventions employed by Kidd et al (2013), Kidd et al (2014) and Pasnak, et al (2015). The children worked on completing, filling in, reproducing and creating patterns of numbers, shapes, or letters, rotations of an object and objects.…”
Section: Methodsmentioning
confidence: 99%
“…After four months of this parallel instruction on either patterns or academic subject matter, the children taught patterning outscored the others on Diagnostic Achievement Battery measures of mathematics and written language. More recently, researchers have compared first grade children randomly assigned to receive thrice weekly instruction for approximately five months on either complex patterns similar to those Hendricks et al (2006) employed, mathematics, reading, or social studies (Kidd, et al 2013;Kidd, et al 2014;Pasnak, et al 2015). Although results varied somewhat across experiments and tests, the children taught patterning scored as well or better on two standardized tests of mathematics than those taught mathematics or social studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation